Overview on Strategies and Approaches for FPGA Programming - Tole Sutikno; Nik Rumzi Nik Idris; Aiman Zakwan Jidin (Universitas Ahmad Dahlan, 2014)
This paper presents an overview of strategies and approaches for FPGA programming. At first, design entry methods are briefly introduced. Then, the concepts of FPGA programming in some perspective viewpoints, such as: execution perspective, modelling perspective, programming style perspective, construction methodology perspective and synthesis perspective will be explained. Finally, the principle of VHDL programming use synchronization-evolution-action approach is introduced.